A polymer, a liquid crystal alignment agent, a liquid crystal alignment film and a liquid crystal display element

By using polymers with specific diamine structures to prepare liquid crystal alignment agents, the dust production and static problems of the surface friction method of the liquid crystal alignment film are solved, and the mechanical strength and transmittance are improved, thereby achieving a more uniform liquid crystal orientation.

CN119751869APending Publication Date: 2025-04-04WUHAN ROUXIAN SCIENCE & TECHNOLOGY CO LTD +2
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202510011499.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-04
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The surface friction method of the existing liquid crystal alignment film has problems of dust production and static electricity, and high-definition sunshaping causes uneven concave and convexity of the substrate, making it difficult to achieve uniform liquid crystal orientation.

Method used

The liquid crystal alignment agent is prepared using polymers containing a specific diamine structure, and the mechanical strength of the liquid crystal alignment film is increased through the form of a block copolymer, and the optical path dispersion is reduced through aromatic heterocycles and the transmittance is improved.

Benefits of technology

The mechanical strength and transmittance of the liquid crystal orientation film are improved, the dust production and static electricity problems of friction are solved, and a more uniform liquid crystal orientation is achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119751869A_ABST
    Figure CN119751869A_ABST
Patent Text Reader

Abstract

The present invention discloses a liquid crystal alignment agent, including a polyamic acid-polyimide copolymer and an organic solvent. The block polymer in the polyamic acid-polyimide copolymer is prepared by a diamine component comprising a structure shown in the following formula (1) and at least one dianhydride component selected from cyclobutane tetracarboxylic dianhydride shown in the following formula (3-1) and 1,3-dimethylcyclobutane tetracarboxylic dianhydride shown in the following formula (3-2); In formula (1), X1 and X2 each independently represent a single bond or an alkyl group with 1 to 6 carbon atoms; Y1 and Y2 each independently represent one or more of -NHCO-, -CONH-, -OCO-, -COO-; Ar is a nitrogen-containing heterocyclic structure. The present invention can provide a liquid crystal alignment film for a lateral electric field driven liquid crystal display element endowed with high mechanical strength and high transmittance and a liquid crystal display element having the liquid crystal alignment film.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of liquid crystal display, and more specifically, to a polymer, a liquid crystal alignment agent, a liquid crystal alignment film and a liquid crystal display element. Background Art

[0002] Liquid crystal display elements are known as lightweight, thin, and low-power-consuming display devices, and have been used in large-size televisions and the like in recent years, achieving remarkable development.

[0003] A liquid crystal display element is formed by sandwiching a liquid crystal layer between a pair of transparent substrates having electrodes, for example. In addition, in a liquid crystal display element, an organic film formed of an organic material is used as a liquid crystal alignment film to allow liquid crystal to exhibit a desired alignment state between the substrates.

[0004] Liquid crystal alignment films are mainly formed by coating a liquid crystal alignment agent (also called a liquid crystal alignment treatment agent) containing a polyimide polymer on a substrate and baking it. As an alignment treatment method for a liquid crystal alignment film for imparting alignment control capability, a rubbing alignment method and a photo-alignment method are commonly used.

[0005] However, the brushing method of rubbing the surface of the liquid crystal alignment film formed of polyimide or the like has the problem of dust generation and static electricity generation. In addition, due to the high definition of liquid crystal display elements in recent years, the unevenness caused by the electrodes on the corresponding substrate or the switching active elements for liquid crystal driving, it is sometimes impossible to rub the surface of the liquid crystal alignment film evenly with a cloth, and it is impossible to achieve uniform liquid crystal orientation. Therefore, as another orientation treatment method of the liquid crystal alignment film without brushing, the photo-alignment method is actively studied.

[0006] As the main photo-orientation method, a decomposition-type photo-orientation method is known. For example, a polyimide film is irradiated with polarized ultraviolet rays, and the polarization direction dependence of ultraviolet absorption of the molecular structure is utilized to cause anisotropic decomposition. In addition, the liquid crystal is oriented by the polyimide remaining without decomposition. Compared with the liquid crystal orientation film prepared by the rubbing orientation method, the liquid crystal orientation film prepared by the photo-orientation method does not have the problems of dust generation and static electricity, but it is expected to obtain a liquid crystal display element with higher performance. Summary of the invention

[0007] An object of the present invention is to solve at least the above problems and to provide at least the advantages which will be described hereinafter.

[0008] Another object of the present invention is to provide a liquid crystal alignment agent comprising a polymer. Since the polymer has an organic group of a diamine as shown in formula (1), the introduction of a planar aromatic ring can improve the compactness of the molecular chain stacking and enhance the intermolecular interaction of the polymer. The liquid crystal alignment agent is prepared in a block form, which can improve the mechanical strength of the liquid crystal alignment film. At the same time, the aromatic heterocyclic ring has a high molar refractive index, which can reduce the dispersion of light when passing through the liquid crystal alignment film, thereby improving the transmittance of the liquid crystal alignment film and the liquid crystal display element prepared using the liquid crystal alignment film.

[0009] In order to achieve these purposes and other advantages according to the present invention, the first aspect of the present invention provides a polymer, which is prepared from a diamine component comprising a structure represented by the following formula (1) and a dianhydride component comprising a structure selected from the following formula (3-1) and / or a structure represented by the following formula (3-2);

[0010]

[0011] In formula (1), X1 and X2 each independently represent a single bond or an alkyl group having 1 to 6 carbon atoms; Y1 and Y2 each independently represent one or more of -NHCO-, -CONH-, -OCO-, and -COO-; the structure represented by Ar is one or more structures selected from the following formulas (2-1) to (2-4);

[0012]

[0013] Preferably, the diamine component of the structure represented by formula (1) is selected from one or more of the following structures:

[0014]

[0015]

[0016] Preferably, the molar ratio of the diamine component to the dianhydride component is (1.08-1.15):1.

[0017] The second aspect of the present invention provides a liquid crystal alignment agent, comprising a polyamic acid-polyimide copolymer and an organic solvent, wherein the polyamic acid-polyimide copolymer is prepared by reacting a polymer, a dianhydride compound of the structure of formula (3-1) or (3-2), and a substituted or unsubstituted diamine compound having 4 to 18 carbon atoms.

[0018] Preferably, the molar ratio of the dianhydride component in the polymer to the dianhydride compound is 1:(3-5).

[0019] Preferably, the molar ratio of the dianhydride compound to the diamine compound is 1:(1.02-1.08).

[0020] Preferably, the diamine compound comprises a diamine compound containing a nitrogen heterocyclic ring, a diamine compound containing an ether bond, and a diamine compound containing a urethane bond in a molar ratio of 1:(1.3-1.8):(1.8-2.2).

[0021] The present invention thirdly provides a liquid crystal alignment film for a transverse electric field driven liquid crystal display element, which is obtained by using the above-mentioned liquid crystal alignment agent.

[0022] A fourth aspect of the present invention provides a method for preparing a liquid crystal alignment film for a lateral electric field driven liquid crystal display element, comprising the following steps:

[0023] Step [I], coating the liquid crystal alignment agent on a substrate having a conductive film for lateral electric field driving to form a coating film;

[0024] Step [II], irradiating the coating film obtained in step [I] with polarized ultraviolet rays; and

[0025] In step [III], the coating film obtained in step [II] is heated.

[0026] According to a fifth aspect of the present invention, there is provided a transverse electric field driven liquid crystal display element, which includes a liquid crystal alignment film.

[0027] The present invention has at least the following beneficial effects:

[0028] Due to the organic group of the diamine shown in formula (1), the introduction of the planar aromatic ring can improve the compactness of the molecular chain stacking, enhance the intermolecular interaction of the polymer, and prepare the liquid crystal alignment agent in the form of blocks, which can improve the mechanical strength of the liquid crystal alignment film. At the same time, the aromatic heterocyclic ring has a high molar refractive index, which can reduce the dispersion of the light path when passing through the liquid crystal alignment film, thereby improving the transmittance of the liquid crystal alignment film and the liquid crystal display element prepared using the liquid crystal alignment film.

[0029] Other advantages, objectives and features of the present invention will be embodied in part through the following description, and in part will be understood by those skilled in the art through study and practice of the present invention. DETAILED DESCRIPTION

[0030] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0031] The liquid crystal aligning agent of the present invention is a mixture of a diamine component including a diamine represented by the above formula (1), a polymer including at least one component selected from cyclobutane tetracarboxylic dianhydride represented by the above formula (3-1) and 1,3-dimethylcyclobutane tetracarboxylic dianhydride represented by the above formula (3-2), a dianhydride compound having a structure of the above formula (3-1) or (3-2), a polyamic acid-polyimide copolymer formed by a substituted or unsubstituted diamine compound having 4 to 18 carbon atoms, and an organic solvent. The following describes each condition in detail.

[0032] <Polymer>

[0033] The polymer used in the present invention is a polymer obtained from a diamine component including a diamine represented by the following formula (1) and at least one component selected from cyclobutanetetracarboxylic dianhydride represented by the following formula (3-1) and 1,3-dimethylcyclobutanetetracarboxylic dianhydride represented by the following formula (3-2). The polymer of the present invention is a block copolymer in a liquid crystal aligning agent.

[0034]

[0035] In formula (1), X1 and X2 represent a single bond or an alkyl group having 1 to 6 carbon atoms, Y1 and Y2 each independently represent one or more of -NHCO-, -CONH-, -OCO- and -COO-; the structure represented by Ar is at least one structure selected from the group consisting of the structures represented by each of the following formulae (2-1) to (2-4);

[0036]

[0037] In an embodiment of the present invention, the polymer of the present invention, as a component of a liquid crystal alignment agent, is applied to a liquid crystal alignment film for a lateral electric field driven liquid crystal display element. Due to the organic group having a diamine shown in formula (1), the introduction of a planar characteristic aromatic ring can improve the compactness of the molecular chain stacking and enhance the intermolecular interaction of the polymer. The liquid crystal alignment agent is prepared in a block form, which can improve the mechanical strength of the liquid crystal alignment film. At the same time, the aromatic heterocycle has a high molar refractive index, which can reduce the dispersion of the light path when passing through the liquid crystal alignment film, thereby improving the transmittance of the liquid crystal alignment film and the liquid crystal display element prepared using the liquid crystal alignment film.

[0038] By adjusting the molar ratio of the diamine component to the dianhydride component and controlling the size of the polymer molecular weight, better mechanical strength can be achieved. In an embodiment of the present invention, the molar ratio of the diamine component to the dianhydride component is (1.08-1.15):1.

[0039] In the embodiment of the present invention, from the perspective of the source of the diamine monomer raw material and the ease of synthesis, the diamine component of the structure represented by the above formula (1) preferably includes diamines represented by the following formulas (DA-1) to (DA-4):

[0040]

[0041] In the embodiment of the present invention, the method for synthesizing the diamine represented by formula (1) is not particularly limited. For example, a method can be mentioned in which a dinitro compound represented by the following formula (5) is used and its nitro group is converted into an amino group by a reduction reaction.

[0042]

[0043] In formula (5), the definitions of X1, Y1, X2, Y2, and Ar are the same as those of X1, Y1, X2, Y2, and Ar in the above formula (1).

[0044] The catalyst used in the above-mentioned reduction reaction is preferably an activated carbon-supported metal that can be obtained as a commercial product, for example, palladium-activated carbon, platinum-activated carbon, rhodium-activated carbon, etc. can be listed. In addition, palladium hydroxide, platinum oxide, Raney nickel, etc. can also be used, and it is not necessary to be an activated carbon-supported metal catalyst. Generally, widely used palladium-activated carbon is easy to obtain good results, so it is preferred.

[0045] In order to carry out the reduction reaction more effectively, the reaction is sometimes carried out in the presence of activated carbon. In this case, the amount of activated carbon used is not particularly limited, and is preferably in the range of 1 to 30% by mass, more preferably 10 to 20% by mass, relative to the dinitro compound of the above formula (5). For the same reason, the reaction is sometimes carried out under pressure. In this case, in order to avoid the reduction of the benzene ring, the reaction is carried out in the range of atmospheric pressure to 20 atmospheres of pressure. The reaction is preferably carried out in the range of atmospheric pressure to 10 atmospheres of pressure.

[0046] As for the solvent used in the synthesis of the specific diamine, any solvent that does not react with the raw materials can be used without limitation. For example, aprotic polar organic solvents (dimethylformamide, dimethyl sulfoxide, N-methyl-2-pyrrolidone, etc.); ethers (diethyl ether, diisopropyl ether, tert-butyl methyl ether, cyclopentyl methyl ether, tetrahydrofuran, dioxane, etc.); aliphatic hydrocarbons (pentane, hexane, heptane, petroleum ether, etc.); aromatic hydrocarbons (benzene, toluene, xylene, mesitylene, chlorobenzene, dichlorobenzene, nitrobenzene, tetralin, etc.); halogen hydrocarbons (chloroform, dichloromethane, carbon tetrachloride, dichloroethane, etc.); lower fatty acid esters (methyl acetate, ethyl acetate, butyl acetate, methyl propionate, etc.); nitriles (acetonitrile, propionitrile, butyronitrile, etc.), etc. can be used. One or more of these solvents can be used. In addition, the solvent can be dried using an appropriate dehydrating agent or drying agent and used as a non-aqueous solvent.

[0047] The amount of the solvent used (reaction concentration) is not particularly limited, but is 0.1 to 100 times by mass, preferably 0.5 to 30 times by mass, and more preferably 1 to 10 times by mass, relative to the dinitro compound of the above formula (5).

[0048] The reaction temperature is not particularly limited, but is in the range of -100° C. to the boiling point of the solvent used, and is preferably -50 to 150° C. The reaction time is usually 0.05 to 350 hours, and preferably 0.5 to 100 hours.

[0049] The method for synthesizing the dinitro compound of formula (5) is not particularly limited. For example, as shown in the following reaction process, a heterocyclic aromatic diacid and a p-nitrophenyl alkyl alcohol are reacted in the presence of a condensing agent and a catalyst to obtain the dinitro compound represented by formula (5).

[0050]

[0051] In the above reaction process, the definitions of X1, Y1, X2, Y2, and Ar are the same as those of X1, Y1, X2, Y2, and Ar in the above formula (1). Z1 represents an amino group or a hydroxyl group: when Z1 is an amino group, Y1 is -NHCO- and Y2 is -CONH-; when Z1 is a hydroxyl group, Y1 is -OCO- and Y2 is -COO-.

[0052] Examples of the condensing agent used in the above reaction process are not particularly limited as long as they can be synthesized, and can include triphenyl phosphite, dicyclohexylcarbodiimide, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride, N,N'-carbonyldiimidazole, dimethoxy-1,3,5-triazinylmethylmorpholine, O-(benzotriazol-1-yl)-N,N,N',N'-tetramethyluronium tetrafluoroborate, O-(benzotriazol-1-yl)-N,N,N',N'-tetramethyluronium hexafluorophosphate, (2,3-dihydro-2-thia-3-benzoxazolyl)phosphonic acid diphenyl ester, etc. The amount of the condensing agent used is preferably 1 to 1.5 times the amount of carboxyl groups, and particularly preferably 1 to 1.25 times the amount of moles. As the catalyst, triethylamine, pyridine, 4-dimethylaminopyridine, 1-hydroxybenzotriazole, 1-hydroxy-7-azidobenzotriazole, triethylenediamine or the like can be used.

[0053] <Dianhydride Compound>

[0054] From the preparation components used as liquid crystal aligning agents, specific examples include polyamic acid, polyamic acid ester, polyimide, polyurea, polyamide, etc. From the perspective of the solubility of the liquid crystal aligning agent in a solvent, a polyimide precursor is more preferred. The dianhydride component in the polyimide precursor is derived from a dianhydride compound of a tetracarboxylic acid derivative containing at least one structure selected from the formula (3-1) and (3-2).

[0055]

[0056] <Diamine Compound>

[0057] The diamine component in the polyimide precursor is derived from a diamine compound not containing the structure of formula (1), and its structure is not particularly limited. The diamine compound can be appropriately selected depending on the degree of desired properties, and one type may be present in the same polymer, or two or more types may be mixed.

[0058] The structures of the diamine compounds are shown below, but the present invention is not limited to these structures.

[0059]

[0060] The diamine component in the polyimide precursor is a substituted or unsubstituted diamine compound having 4 to 18 carbon atoms. The molar ratio of the dianhydride compound to the diamine compound is 1:(1.02 to 1.08).

[0061] Preferably, the diamine compound comprises a nitrogen-containing heterocyclic diamine compound, a diamine compound containing an ether bond, and a diamine compound containing a carbamate bond in a molar ratio of 1:(1.3-1.8):(1.8-2.2). The introduction and combined use of the diamine structures shown below can obtain a liquid crystal display element with better orientation.

[0062] Specifically:

[0063]

[0064] <Liquid crystal alignment agent>

[0065] The liquid crystal aligning agent of the present invention contains a polymer obtained from a diamine component containing a diamine represented by the above formula (1) and a dianhydride component containing at least one selected from cyclobutanetetracarboxylic dianhydride represented by the above formula (3-1) and 1,3-dimethylcyclobutanetetracarboxylic dianhydride represented by the above formula (3-2).

[0066] The liquid crystal alignment agent of the present invention comprises a polymer, a dianhydride compound of the structure of formula (3-1) or (3-2), a substituted or unsubstituted diamine compound having 4 to 18 carbon atoms, which react to form a polyamic acid-polyimide copolymer and an organic solvent. The molar ratio of the dianhydride component in the polymer to the dianhydride compound in the liquid crystal alignment agent of the present invention is 1:(3 to 5).

[0067] From the viewpoint of the source of the diamine monomer raw material and the ease of synthesis, the diamine component of the diamine represented by the above formula (1) preferably includes diamines represented by the above formulae (DA-1) to (DA-4).

[0068] The molecular weight of the polyamic acid-polyimide copolymer used in the present invention is preferably 2,000 to 500,000, more preferably 5,000 to 300,000, and even more preferably 10,000 to 100,000 in terms of weight average molecular weight.

[0069] As the polyamic acid-polyimide copolymer used in the present invention, the ring closure rate (also referred to as imidization rate) of the amic acid group in the polyamic acid-polyimide copolymer does not necessarily have to be 100%, and can be arbitrarily adjusted according to the use and purpose. Regarding the polyamic acid-polyimide copolymer of the present invention, from the viewpoint of liquid crystal orientation, preferably 10 to 100%, more preferably 10 to 90%, and further preferably 20 to 80%.

[0070] Examples of a method for imidizing a polyamic acid-polyimide copolymer include thermal imidization in which a solution of a polyamic acid-polyimide copolymer is directly heated, and catalytic imidization in which a catalyst is added to a solution of a polyamic acid-polyimide copolymer.

[0071] The liquid crystal alignment agent of the present invention contains the above polymer, and in the liquid crystal alignment film obtained after the curing and heating process, the aromatic ring planar structure can produce tight interchain stacking and increase the interaction between molecules, thereby improving the mechanical strength of the liquid crystal alignment film. At the same time, the aromatic ring containing heteroatoms has a high molar refractive index, thereby reducing dispersion, and obtaining a liquid crystal alignment film with high transmittance and its corresponding liquid crystal display element.

[0072] Liquid crystal alignment agent is used to make liquid crystal alignment film, and from the viewpoint of forming a uniform film, the form of coating liquid is generally adopted. The liquid crystal alignment agent of the present invention is also preferably a coating liquid containing the aforementioned polyamic acid-polyimide copolymer component and an organic solvent that can dissolve the polyamic acid-polyimide copolymer component. At this time, the concentration of the polyamic acid-polyimide copolymer in the liquid crystal alignment agent can be appropriately changed according to the setting of the thickness of the coating film to be formed. From the viewpoint of forming a uniform and defect-free coating film, the polyamic acid-polyimide copolymer accounts for preferably more than 1% by mass in the entire liquid crystal alignment agent, and from the viewpoint of the storage stability of the solution, it is preferably set to less than 10% by mass. A particularly preferred concentration is 2 to 8% by mass.

[0073] The organic solvent contained in the liquid crystal alignment agent is not particularly limited if it is an organic solvent in which the polyamic acid-polyimide copolymer component can be uniformly dissolved. If specific examples are given, N,N-dimethylformamide, N,N-dimethylacetamide, N-methyl-2-pyrrolidone, N-ethyl-2-pyrrolidone, dimethyl sulfoxide, γ-butyrolactone, 1,3-dimethylimidazolidinone, methyl ethyl ketone, cyclohexanone, cyclopentanone, etc. can be listed. Among them, N-methyl-2-pyrrolidone, N-ethyl-2-pyrrolidone or γ-butyrolactone is preferably used.

[0074] In addition, for the organic solvent contained in the liquid crystal alignment agent, a mixed solvent formed by a solvent that can improve the coating property and surface smoothness of the coating film when the liquid crystal alignment agent is applied is usually used on the basis of the above-mentioned solvent, and such a mixed solvent is also preferably used in the liquid crystal alignment agent of the present invention. Specific examples of the organic solvents used in combination are listed below, but are not limited to these examples.

[0075] For example, ethanol, isopropanol, 1-butanol, 2-butanol, isobutanol, tert-butanol, 1-pentanol, 2-pentanol, 3-pentanol, 2-methyl-1-butanol, isopentanol, tert-pentanol, 3-methyl-2-butanol, neopentyl alcohol, 1-hexanol, 2-methyl-1-pentanol, 2-methyl-2-pentanol, 2-ethyl-1-butanol, 1-heptanol, 2-heptanol, 3-heptanol, 1-octanol, 2-octanol, 2-ethyl-1-hexanol, cyclohexanol, 1-methylcyclohexanol, 2-methylcyclohexanol, 3-methylcyclohexanol, 1,2-ethanediol, 1,2-propylene glycol, 1,3-propylene glycol, 1,2-butanediol, 1,3- Butanediol, 1,4-butanediol, 2,3-butanediol, 1,5-pentanediol, 2-methyl-2,4-pentanediol, 2-ethyl-1,3-hexanediol, dipropyl ether, dibutyl ether, dihexyl ether, dioxane, ethylene glycol dimethyl ether, ethylene glycol diethyl ether, ethylene glycol dibutyl ether, 1,2-butoxyethane, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, 4-hydroxy-4-methyl-2-pentanone, diethylene glycol methyl ethyl ether, diethylene glycol dibutyl ether, 2-pentanone, 3-pentanone, 2-hexanone, 2-heptanone, 4-heptanone, 3-ethoxybutyl acetate, 1-methylpentyl acetate, 2-ethylbutyl acetate, 2-ethyl 1-(Butoxyethoxy)propanol, propylene glycol monomethyl ether acetate, dipropylene glycol, dipropylene glycol monomethyl ether, dipropylene glycol monoethyl ether, dipropylene glycol dimethyl ether, tripropylene glycol monomethyl ether, ethylene glycol monomethyl ether acetate, ethylene glycol monoethyl ether acetate, ethylene glycol monobutyl ether acetate, ethylene glycol monoacetate, ethylene glycol diacetate Ester, diethylene glycol monoethyl ether acetate, diethylene glycol monobutyl ether acetate, 2-(2-ethoxyethoxy)ethyl acetate, diethylene glycol acetate, triethylene glycol, triethylene glycol monomethyl ether, triethylene glycol monoethyl ether, methyl lactate, ethyl lactate, methyl acetate, ethyl acetate, n-butyl acetate, propylene glycol acetate monoethyl ether, methyl pyruvate, ethyl pyruvate, methyl 3-methoxypropionate, methyl ethyl 3-ethoxypropionate, ethyl 3-methoxypropionate, 3-ethoxypropionic acid, 3-methoxypropionic acid, propyl 3-methoxypropionate, butyl 3-methoxypropionate, methyl lactate, ethyl lactate, n-propyl lactate, n-butyl lactate, isoamyl lactate, and the like.

[0076] The type and content of the solvent can be appropriately selected according to a coating device, coating conditions, coating environment, and the like of the liquid crystal aligning agent.

[0077] The liquid crystal aligning agent of the present invention may also contain additional components other than the polyamic acid-polyimide copolymer and the organic solvent within the scope of not impairing the effect of the present invention. As such additional components, there can be listed: a close adhesion aid for improving the close adhesion between the liquid crystal alignment film and the substrate, and the close adhesion between the liquid crystal alignment film and the sealing material; a cross-linking agent for improving the strength of the liquid crystal alignment film; a dielectric or conductive material for adjusting the dielectric constant and resistance of the liquid crystal alignment film, etc.

[0078] <Method for producing a liquid crystal alignment film> and <Method for producing a liquid crystal display element>

[0079] The method for producing a liquid crystal alignment film of the present invention comprises the following steps:

[0080] Step [I], coating a polymer composition on a substrate having a conductive film for lateral electric field driving, and drying the coating film, wherein the polymer composition comprises a polyamic acid-polyimide copolymer and an organic solvent, wherein the polyamic acid-polyimide copolymer is prepared by reacting a polymer obtained by a diamine component comprising a diamine represented by the above formula (1) and an acid component comprising at least one selected from the group consisting of cyclobutanetetracarboxylic dianhydride represented by the above formula (3-1) and 1,3-dimethylcyclobutanetetracarboxylic dianhydride represented by the above formula (3-2), a dianhydride compound having a structure of the above formula (3-1) or (3-2), and a substituted or unsubstituted diamine compound having 4 to 18 carbon atoms;

[0081] Step [II], irradiating the coating film obtained in step [I] with polarized ultraviolet rays; and

[0082] In step [III], the coating film obtained in step [II] is heated.

[0083] Through the above-mentioned steps, a liquid crystal alignment film for a transverse electric field driven liquid crystal display element to which an alignment control capability is imparted can be obtained, and a substrate having the liquid crystal alignment film can be obtained.

[0084] Furthermore, by preparing a second substrate in addition to the substrate (first substrate) obtained as described above, a transverse electric field driven liquid crystal display element can be obtained.

[0085] In addition to using a substrate without a conductive film for driving a lateral electric field instead of a substrate with a conductive film for driving a lateral electric field, the second substrate having a liquid crystal orientation film endowed with orientation control capability can be obtained by using the above-mentioned steps [I] to [III] (due to the use of a substrate without a conductive film for driving a lateral electric field, for convenience, these are sometimes referred to as steps [I'] to [III'] in this application).

[0086] A method for manufacturing a lateral electric field driven liquid crystal display element comprises:

[0087] Step [IV]: The first substrate and the second substrate obtained above are arranged to face each other so that the liquid crystal alignment films of the first substrate and the second substrate face each other with the liquid crystal interposed therebetween, thereby obtaining a liquid crystal display element. Thus, a transverse electric field driven liquid crystal display element can be obtained.

[0088] Hereinafter, each step [I] to [III] and [IV] included in the production method of the present invention will be described.

[0089] <Process [I]>

[0090] In step [I], a polymer composition containing a polyamic acid-polyimide copolymer and an organic solvent is applied onto a substrate having a conductive film for transverse electric field driving, and then dried to form a coating film.

[0091] <Substrate>

[0092] There is no particular limitation on the substrate, but when the manufactured liquid crystal display element is a transmission type, a substrate with high transparency is preferably used. In this case, there is no particular limitation, and a glass substrate, or a plastic substrate such as an acrylic substrate or a polycarbonate substrate can be used.

[0093] In addition, in consideration of application to a reflective liquid crystal display element, an opaque substrate such as a silicon wafer may be used.

[0094] <Conductive film for lateral electric field driving>

[0095] The substrate has a conductive film for lateral electric field driving.

[0096] When the liquid crystal display element is a transmission type, examples of the conductive film include ITO (Indium Tin Oxide) and IZO (Indium Zinc Oxide), but the conductive film is not limited to these.

[0097] In the case of a reflective liquid crystal display element, examples of the conductive film include materials that reflect light, such as aluminum, but are not limited to these.

[0098] As a method of forming a conductive film on a substrate, a conventionally known method can be used.

[0099] The method for applying the polymer composition onto the substrate having the conductive film for transverse electric field driving is not particularly limited.

[0100] The coating method is generally industrially performed by screen printing, offset printing, flexographic printing or inkjet method, etc. Other coating methods include dipping, roll coating, slit coating, spin coating (spin coating method) or spray coating, and these methods can be used according to the purpose.

[0101] After coating the polymer composition on a substrate having a conductive film for lateral electric field driving, the solvent can be evaporated at 30 to 150° C., preferably 70 to 110° C., using a heating unit such as a hot plate, a heat cycle oven, or an IR (infrared) oven to obtain a coating. When the drying temperature is too low, there is a tendency for the solvent to be insufficiently dried, and when the heating temperature is too high, thermal imidization will occur, resulting in excessive photolysis reaction due to polarized light exposure, thereby impairing the orientation stability. Therefore, from the viewpoint of liquid crystal orientation stability, the drying temperature at this time is preferably a temperature at which the specific polymer is substantially not thermally imidized.

[0102] If the coating film is too thick, it is disadvantageous in terms of power consumption of the liquid crystal display element, and if it is too thin, the reliability of the liquid crystal display element may decrease. Therefore, it is preferably 5 nm to 300 nm, more preferably 10 nm to 150 nm.

[0103] Note that, after step [I] and before the next step [II], a step of cooling the substrate on which the coating film is formed to room temperature may be provided.

[0104] <Process [II]>

[0105] In step [II], the coating obtained in step [I] is irradiated with polarized ultraviolet rays. When the film surface of the coating is irradiated with polarized ultraviolet rays, the substrate is irradiated with polarized ultraviolet rays from a specific direction through a polarizing plate. As the ultraviolet rays used, ultraviolet rays with a wavelength in the range of 100nm to 400nm can be used. Preferably, the optimal wavelength is selected with the aid of a filter or the like depending on the type of coating used. In addition, for example, in order to selectively induce a photolysis reaction, ultraviolet rays with a wavelength in the range of 240nm to 400nm can be selected. As ultraviolet rays, for example, light emitted by a high-pressure mercury lamp or a metal halide lamp can be used.

[0106] The irradiation amount of polarized ultraviolet rays depends on the coating film used. The irradiation amount is preferably set in the range of 1% to 70% of the amount of polarized ultraviolet rays that achieves the maximum value of ΔA (hereinafter also referred to as ΔAmax), and more preferably in the range of 1% to 50%, wherein ΔA is the difference between the ultraviolet absorbance parallel to the polarization direction of the polarized ultraviolet rays and the ultraviolet absorbance perpendicular to the polarization direction of the polarized ultraviolet rays of the coating film.

[0107] <Step [III]>

[0108] In step [III], the coating film irradiated with polarized ultraviolet rays in step [II] is heated. Heating can impart orientation control capability to the coating film.

[0109] The heating may be performed using a heating unit such as a hot plate, a heat circulation oven, or an IR (infrared) oven. The heating temperature may be determined in consideration of a temperature at which the coating film to be used exhibits good liquid crystal alignment stability and electrical properties.

[0110] The heating temperature is preferably within the temperature range in which the polyimide liquid crystal alignment film has good liquid crystal alignment stability. When the heating temperature is too low, there is a tendency that the anisotropy amplification effect caused by heat and thermal imidization are insufficient, and when the heating temperature is excessively higher than the temperature range, there is a tendency that the anisotropy imparted by polarized light exposure will disappear.

[0111] For the same reason as described in step [I], the thickness of the coating formed after heating is preferably 5 nm to 300 nm, more preferably 50 nm to 150 nm. By having the above steps, the manufacturing method of the present invention can efficiently introduce anisotropy into the coating. In addition, a substrate with a liquid crystal alignment film can be efficiently manufactured.

[0112] <Step [IV]>

[0113] Step [IV] is a step in which the substrate (first substrate) having a liquid crystal alignment film on the conductive film for lateral electric field driving obtained in step [III] and the substrate (second substrate) with a liquid crystal alignment film without a conductive film obtained in the above steps [I'] to [III'] are arranged opposite to each other in such a manner that the liquid crystal alignment films of the two are opposite to each other with liquid crystals interposed therebetween, and a liquid crystal unit is produced by a known method to produce a lateral electric field driven liquid crystal display element. It should be noted that steps [I'] to [III'] can be carried out in the same manner as steps [I] to [III] except that a substrate without a conductive film for lateral electric field driving is used instead of a substrate with the conductive film for lateral electric field driving in step [I]. The difference between steps [I] to [III] and steps [I'] to [III'] is only the presence or absence of the conductive film, so the description of steps [I'] to [III'] is omitted.

[0114] If a production example of a liquid crystal unit or a liquid crystal display element is given, the following method can be illustrated: prepare the above-mentioned first substrate and second substrate, spread spacers on the liquid crystal alignment film of one substrate, adhere the other substrate with the liquid crystal alignment film surface as the inner side, and inject liquid crystal under reduced pressure and seal; or, after dripping liquid crystal on the surface of the liquid crystal alignment film with spacers, adhere the substrates and seal. At this time, the substrate on one side preferably uses a substrate with an electrode structure like a comb tooth for lateral electric field driving. The diameter of the spacer at this time is preferably 1μm to 30μm, and more preferably 2μm to 10μm. The diameter of the spacer will determine the distance between a pair of substrates used to clamp the liquid crystal layer, that is, the thickness of the liquid crystal layer.

[0115] In the method for manufacturing a substrate with a coating film of the present invention, a composition of a polyamic acid-polyimide copolymer and an organic solvent is applied on a substrate to form a coating film, and then polarized ultraviolet rays are irradiated. Then, small molecules generated by photolysis are removed by heating, and anisotropy is introduced, thereby manufacturing a substrate with a liquid crystal alignment film having the ability to control liquid crystal orientation.

[0116] The optimal amount of polarized ultraviolet irradiation for efficiently introducing anisotropy into the coating used in the present invention corresponds to the amount of polarized ultraviolet irradiation that makes the photosensitive group in the coating film to undergo photolysis reaction reach the optimal amount. As a result of irradiating the coating used in the present invention with polarized ultraviolet rays, if there are few photosensitive groups that undergo photolysis reaction, a sufficient amount of photoreaction cannot be achieved. Therefore, in the coating used in the present invention, the optimal amount of photosensitive groups that undergo photolysis reaction by irradiation with polarized ultraviolet rays is preferably set to 0.1 mol% to 90 mol% of the polymer film, and more preferably set to 0.1 mol% to 80 mol%.

[0117] For the coating film used in the method of the present invention, the amount of photolysis reaction of the photosensitive group in the polymer main chain is optimized by optimizing the irradiation amount of polarized ultraviolet rays. The appropriate amount of polarized ultraviolet rays can be determined based on the evaluation of the ultraviolet absorption of the coating film used in the present invention.

[0118] That is, for the coating used in the present invention, the ultraviolet absorption in the direction parallel to the polarization direction of the polarized ultraviolet and the ultraviolet absorption in the direction perpendicular to the polarization direction of the polarized ultraviolet are measured respectively after the polarized ultraviolet irradiation. ΔA is evaluated based on the measurement result of ultraviolet absorption, and the ΔA is the difference between the ultraviolet absorbance in the direction parallel to the polarization direction of the polarized ultraviolet and the ultraviolet absorbance in the direction perpendicular to the polarization direction of the polarized ultraviolet in the coating. Then, the maximum value ΔAmax of ΔA that can be achieved in the coating used in the present invention and the amount of polarized ultraviolet irradiation that achieves this value are calculated. In the manufacturing method of the present invention, the amount of polarized ultraviolet irradiation that achieves this ΔAmax is used as a reference to determine the preferred amount of polarized ultraviolet irradiation in the manufacture of the liquid crystal alignment film.

[0119] The temperature range in which the polymer used in the present invention imparts liquid crystal orientation stability can be determined by considering the temperature at which the coating film used exhibits good liquid crystal orientation stability and electrical properties, and can be set according to the temperature range corresponding to the liquid crystal orientation film formed by polyimide or the like in the past. That is, it is preferred to set the heating temperature after polarized ultraviolet irradiation to 150°C to 300°C, and it is more ideal to set it to 180°C to 250°C. By doing so, the coating film used in the present invention will be given greater anisotropy.

[0120] By doing so, the liquid crystal display element provided by the present invention can show high reliability against external stress such as light and heat.

[0121] As described above, the substrate for a lateral electric field driven liquid crystal display element manufactured using the polymer of the present invention or the lateral electric field driven liquid crystal display element having the substrate has excellent reliability and can be suitably used in large-screen and high-definition liquid crystal televisions, etc. In addition, the liquid crystal alignment film manufactured by the method of the present invention has excellent liquid crystal alignment stability and reliability, and can therefore also be used in a variable phase shifter using liquid crystals, which can be suitably used in, for example, an antenna with a variable resonance frequency, etc.

[0122] The present invention is further described in detail below in conjunction with embodiments so that those skilled in the art can implement the invention with reference to the description.

[0123] It should be noted that the experimental methods described in the following embodiments are conventional methods unless otherwise specified, and the reagents and materials can be obtained from commercial channels unless otherwise specified.

[0124] < 1 HNMR measurement>

[0125] Apparatus: Fourier transform superconducting nuclear magnetic resonance apparatus (FT-NMR) "INOVA-400" (manufactured by Varian), 400 MHz.

[0126] Solvents: deuterated chloroform (CDCl3), deuterated dimethyl sulfoxide (DMSO-d6).

[0127] Reference substance: tetramethylsilane (TMS).

[0128] <Viscosity measurement>

[0129] In the synthesis example, the viscosity of the polymer solution was measured using a rheometer DHR1 (manufactured by TA Instruments, USA) under the conditions of a sample volume of 0.5 mL, a lamina (10, 40 mm), and a temperature of 25°C.

[0130] <Synthesis of diamine monomer>

[0131] <Synthesis example 1>

[0132] Synthesis of DA-1

[0133] Step S1: N 2 ,N 5 -Synthesis of Bis(4-nitrophenylethyl)pyridine-2,5-dicarboxamide (DA-1-1)

[0134]

[0135] Weigh p-nitrophenylethylamine (16.78g, 101mmol), pyridine-2,5-dicarboxylic acid (8.36g, 50mmol) and dissolve in dichloromethane (200mL), then add 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride EDCI (19.75g, 103mmol) and 4-dimethylaminopyridine DMAP (18.33g, 150mmol), and stir the reaction for 12h under nitrogen atmosphere at room temperature. The reaction solution was washed with saturated ammonium chloride solution and saturated brine in sequence, dried with anhydrous sodium sulfate, and then dried under reduced pressure at 40°C to remove the solvent. After the crude product was washed with ethanol, the solid was dissolved in 50mL ethyl acetate at 70°C, and 50mL ethanol was added. After cooling, it was filtered, washed with ethanol again and vacuum dried to finally obtain a light yellow powder solid product DA-1-1 (18.07g, yield 78%).

[0136] 1 H NMR (400MHz, CDCl3): δ9.08(1H),8.98(1H),8.44(2H),8.13(1H),8.15(4H),7.51(4H),3.38(2H),3.33(2H),2.76(4H).

[0137] Step S2: N 2 ,N 5 -Synthesis of Bis(4-aminophenylethyl)pyridine-2,5-dicarboxamide (DA-1)

[0138]

[0139] DA-1-1 (10.00 g, 21.6 mmol) was dissolved in tetrahydrofuran (200 g), 5% mass of palladium-carbon (0.2 g) was added, and the mixture was stirred for 2 h under hydrogen atmosphere at room temperature. 1600 g of tetrahydrofuran was added to the reaction solution, and the palladium-carbon was removed by filtration. After concentration, the solution was precipitated and filtered in n-hexane. The solid was washed and dried to obtain a white solid product DA-1 (7.84 g, yield 90%).

[0140] 1 H NMR (400MHz, DMSO-d6): δ9.08(1H),8.98(1H),8.44(2H),8.13(1H),6.84(4H),6.50(4H),4.93(4H),3.37(2H),3.23(2H),2.65(4H).

[0141] <Synthesis example 2>

[0142] Synthesis of DA-2

[0143] Step S1: Synthesis of bis(4-nitrophenylbutyl)-2,5-pyrazinedicarboxylate (DA-2-1)

[0144]

[0145] Weigh 4-(4-nitrophenyl)-1-butanol (19.72g, 101mmol) and 2,5-pyrazinedicarboxylic acid (8.41g, 50mmol) and dissolve them in dichloromethane (200mL), then add EDCI (19.75g, 103mmol) and DMAP (18.33g, 150mmol), and stir the reaction for 12h under nitrogen atmosphere at room temperature. The reaction solution was washed with saturated ammonium chloride solution and saturated brine in sequence, dried with anhydrous sodium sulfate, and then dried under reduced pressure at 40°C to remove the solvent. After the crude product was washed with ethanol, the solid was dissolved in 50mL of ethyl acetate at 70°C, and 50mL of ethanol was added. After cooling, it was filtered, washed with ethanol again and dried in vacuo to finally obtain a light yellow powder solid product DA-2-1 (19.59g, yield 75%).

[0146] 1 H NMR (400MHz, CDCl3): δ10.11(2H),8.14(4H),7.52(4H),4.32(4H),2.62(4H),1.90(4H),1.62(4H).

[0147] Step S2: Synthesis of bis(4-aminophenylbutyl)-2,5-pyrazinedicarboxylate (DA-2)

[0148]

[0149] DA-1-1 (10.00 g, 19.1 mmol) was dissolved in tetrahydrofuran (200 g), 5% mass of palladium-carbon (0.2 g) was added, and the mixture was stirred for 2 h under hydrogen atmosphere at room temperature. 1600 g of tetrahydrofuran was added to the reaction solution, and the palladium-carbon was removed by filtration. After concentration, the solution was precipitated and filtered in n-hexane. The solid was washed and dried to obtain a white solid product DA-2 (7.70 g, yield 87%).

[0150] 1 H NMR (400MHz, DMSO-d6): δ10.11(2H), 6.85(4H), 6.50(4H), 4.91(4H), 4.32(4H), 2.62(4H), 1.91(4H), 1.62(4H).

[0151] <Synthesis example 3>

[0152]

[0153] Add p-nitrophenylethanol (16.71 g, 100 mmol) into dichloromethane (DCM) solvent, then add 0.1 mol of carbonyldiimidazole (CDI), and reflux for 6 hours. After the reaction, slowly cool to room temperature, add 0.1 mol of p-nitrophenylethylamine to the system, and react at room temperature for 12 hours. After the reaction, remove the solvent by distillation under reduced pressure, add ethanol and stir for 2 hours, filter, and collect the filter cake to obtain DB-1-1 compound.

[0154] Add 0.1 mol of DB-1-1 compound into DMF, stir to dissolve, then add catalytic amount of Pd / C, react at room temperature for 24 hours under H2 atmosphere. After the reaction is completed, filter, pour the filtrate into pure water and stir for 1 hour, filter again, collect the filter cake, and dry to obtain DB-1 compound.

[0155] 1 H NMR (400MHz, DMSO-d6): δ6.92(4H), 6.76(1H), 6.45(4H), 4.91(4H), 4.21(2H), 3.03(2H), 2.84(2H), 2.62(2H).

[0156] <Preparation of Liquid Crystal Alignment Agent>

[0157] The compound structures are shown in Table 1.

[0158] Table 1

[0159]

[0160] <Preparation Example 1>

[0161] DA-1 (1.977 g, 4.90 mmol) was weighed into a 50 mL four-necked flask equipped with a stirrer and a nitrogen inlet tube, and 17.79 g of NMP was added, and the mixture was dissolved while stirring while nitrogen was supplied until it became clear. CA-1 (1.008 g, 4.50 mmol) was added to the diamine solution under stirring, and then 9.08 g of NMP was added, and the mixture was stirred at 25°C for 12 hours under a nitrogen atmosphere to obtain polymer A1.

[0162] DB-1 (5 mmol), DB-2 (5 mmol), DB-3 (7.5 mmol) were added to polymer A1, and 31.89 g of NMP was added, and the mixture was dissolved by stirring while nitrogen was supplied until it was clear. CA-1 (3.811 g, 17 mmol) was added to the above solution under stirring, and then 34.30 g of NMP was added, and the mixture was stirred at 25° C. for 12 hours under a nitrogen atmosphere to obtain a polyamic acid-polyimide copolymer solution having a viscosity of 121 mPa·s at a temperature of 25° C.

[0163] 7.0 g of the polyamic acid-polyimide copolymer solution was taken out and added to a 50 mL conical flask equipped with a stirrer, 7.0 g of NMP and 6.0 g of butyl cellosolve BCS were added, and the mixture was stirred at room temperature for 2 hours to obtain a liquid crystal aligning agent (A-1).

[0164] The preparation methods of the liquid crystal alignment agents of Preparation Examples 2 to 6 are the same as those of Preparation Example 1. The formula and dosage of the polyamic acid-polyimide copolymer solution are shown in Table 2, and the dosage is in mmol.

[0165] The liquid crystal alignment agent formula and dosage of the preparation of comparative example 1 are the same as those of preparation example 1, wherein the different preparation steps are: DA-1 (4.90mmol), DB-1 (5mmol), DB-2 (5mmol), DB-3 (7.5mmol) are mixed, NMP49.69g is added, and nitrogen is supplied while stirring to dissolve until it is clear. CA-1 (21.5mmol) is added to the above solution under stirring, and then NMP43.37g is added, and the mixture is stirred at 25°C for 12 hours under a nitrogen atmosphere to obtain a polyamic acid-polyimide copolymer solution.

[0166] The liquid crystal alignment agent formula and dosage of the preparation of comparative example 2 are the same as those of preparation example 1, except that DB-1 (1.467 g, 4.90 mmol) is weighed into a 50 mL four-necked flask with a stirring device and a nitrogen inlet tube, 13.20 g of NMP is added, and the mixture is dissolved until clear while nitrogen is delivered. CA-1 (1.008 g, 4.50 mmol) is added to the diamine solution under stirring, and then 9.08 g of NMP is added, and the mixture is stirred at 25 ° C for 12 hours under a nitrogen atmosphere to obtain polymer A'-2. DB-1 (5 mmol), DB-2 (5 mmol), and DB-3 (7.5 mmol) are added to polymer A'-2, and 31.89 g of NMP is added, and the mixture is dissolved until clear while nitrogen is delivered and stirred. CA-1 (3.811 g, 17 mmol) and 34.30 g of NMP were added to the solution under stirring, and the mixture was stirred at 25° C. for 12 hours under a nitrogen atmosphere to obtain a polyamic acid-polyimide copolymer solution having a viscosity of 145 mPa·s at 25° C.

[0167] Table 2

[0168]

[0169] <Example 1>

[0170] Preparation of Liquid Crystal Alignment Film

[0171] The liquid crystal alignment agent obtained in Preparation Example 1 was coated on an ITO glass substrate by spin coating, and baked at about 100°C for 180 seconds to volatilize the solvent, and then baked at 200°C for 45 minutes to imidize the polyamic acid; then, an exposure device manufactured by Ushio: APL-L01212S1-AXH01 was used to expose the substrate in a direction perpendicular to the substrate with 254nm polarized light, with an integrated light amount of 200-400mJ / cm 2 The PI film was exposed. The exposed film was baked at 200°C for 45 minutes to volatilize the small molecules cracked after exposure, forming a 100nm thick liquid crystal alignment film.

[0172] In Examples 2-6, the liquid crystal alignment agents of Preparation Examples 2 to 6 were used to prepare liquid crystal alignment films, and in Comparative Examples 1 to 2, the liquid crystal alignment agents of Preparation Comparative Examples 1 to 2 were used to prepare liquid crystal alignment films.

[0173] The liquid crystal alignment films made of the liquid crystal alignment agents obtained in Preparation Examples 1 to 6 and Preparation Comparative Examples 1 to 2 were evaluated. The evaluation results are shown in Table 3.

[0174] Table 3

[0175] serial number Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 Comparative Example 1 Comparative Example 2 Liquid crystal alignment agent A-1 A-2 A-3 A-4 A-5 A-6 A’-1 A’-2 Haze(%) 0.25 0.22 0.22 0.21 0.18 0.16 0.62 0.53

[0176] As shown in Table 3, the haze of the liquid crystal alignment film in Examples 1 to 6 was less than 0.5%, which was good, and thus the display quality of the liquid crystal display element using the film was excellent. However, in Comparative Example 1, the haze was greater than 0.5%, which was poor.

[0177] <Evaluation Method of Mechanical Strength>

[0178] The liquid crystal alignment film on the ITO glass substrate after the alignment process was selected, and the liquid crystal alignment film was from Examples 1 to 6 and Comparative Examples 1 to 2, and was rubbed on a friction device, with the roller speed set to 1000 rpm, the speed of the substrate glass where the liquid crystal alignment film was located to 20 mm / s, the friction cloth press-in amount to 0.5 mm, and rubbed continuously for 16 times. After the liquid crystal alignment film was rubbed, it was cleaned with an air gun and then tested for haze on a haze tester. The case where the haze value was less than 0.5% was defined and evaluated as "good" in mechanical strength, and the case where the haze value was more than 0.5% was defined and evaluated as "poor" in mechanical strength.

[0179] <Application Example 1>

[0180] A liquid crystal cell having a liquid crystal display element structure of the FFS mode was produced.

[0181] First, prepare a substrate with electrodes. The substrate is a glass substrate with a size of 30 mm × 35 mm and a thickness of 0.7 mm. On the substrate, as the first layer, an ITO electrode constituting a counter electrode is formed on the entire surface. On the counter electrode of the first layer, as the second layer, a SiN (silicon nitride) film formed by a CVD method is formed. The film thickness of the SiN film of the second layer is 500 nm, and it functions as an interlayer insulating film. On the SiN film of the second layer, as the third layer, a comb-shaped pixel electrode formed by patterning the ITO film is arranged to form two pixels, the first pixel and the second pixel. The size of each pixel is 10 mm in length and about 5 mm in width. At this time, the counter electrode of the first layer and the pixel electrode of the third layer are electrically insulated due to the action of the SiN film of the second layer.

[0182] The pixel electrode of the third layer has a comb-like shape composed of a plurality of "<"-shaped electrode elements with a bent central portion. The width of each electrode element in the width direction is 10μm, and the interval between the electrode elements is 10μm. The pixel electrode forming each pixel is composed of a plurality of "<"-shaped electrode elements with a bent central portion, so the shape of each pixel is not a rectangle, but a shape similar to a bold "<" character that is bent in the central portion like the electrode elements. Furthermore, each pixel is divided into upper and lower parts with the central bent portion as the boundary, and has a first area on the upper side of the bent portion and a second area on the lower side.

[0183] When comparing the first area and the second area of ​​each pixel, the electrode elements constituting the pixel electrodes are formed in different directions. That is, when the line segment direction of the polarization plane of the polarized ultraviolet rays described later projected onto the substrate is used as a reference, the electrode elements of the pixel electrode are formed at an angle of +10° (clockwise) in the first area of ​​the pixel, and the electrode elements of the pixel electrode are formed at an angle of -10° (clockwise) in the second area of ​​the pixel. That is, the first area and the second area of ​​each pixel are constructed as follows: the directions of the rotation action (plane switching) of the liquid crystal in the substrate surface induced by applying a voltage between the pixel electrode and the counter electrode are opposite to each other.

[0184] Next, the liquid crystal alignment agent obtained in Preparation Example 1 was coated on the prepared substrate with electrodes using a coater method. The coated film was baked at about 100°C for 180 seconds to evaporate the solvent, and then baked at 200°C for 45 minutes to imidize the polyamic acid. Next, an exposure device manufactured by Ushio: APL-L01212S1-AXH01 was used to expose the film perpendicular to the substrate using 254nm polarized light with an integrated light intensity of 300 to 600mJ / cm 2The PI film is exposed. The exposed film is baked at 200°C for 45 minutes to volatilize the small molecules cracked after exposure to form an alignment layer.

[0185] On the basis of the FFS electrode substrate with the liquid crystal alignment film, a glass substrate with a columnar spacer of 4μm in height is used as the opposite substrate to apply the liquid crystal alignment agent and the alignment treatment to obtain a substrate with a polyimide liquid crystal alignment film. A circle of uniform sealant is applied on the substrate by gas extrusion to bond the substrate and seal the liquid crystal; a high-precision titration device is used to drip the liquid crystal RXA10300 (negative liquid crystal manufactured by Chengzhi Yonghua Company), and the two substrates are bonded under 1Pa of pressure; a 365nm wavelength UV light is used to irradiate the sealant in the bonded substrate, and the accumulated light quantity is 5000-20000mJ / cm 2 , so that its photoinitiator reacts; the UV-cured substrate is baked at a temperature of 100° C. for 2 hours to fully cure the frame glue; and an FFS mode liquid crystal unit is obtained.

[0186] Application Examples 2-6 use the liquid crystal alignment agents of Preparation Examples 2 to 6 to prepare liquid crystal units, and Application Comparative Examples 1 to 2 use the liquid crystal alignment agents of Preparation Comparative Examples 1 to 2 to prepare liquid crystal units.

[0187] The liquid crystal cells prepared by the liquid crystal alignment agents obtained in Preparation Examples 1 to 6 and Comparative Preparation Examples 1 to 2 were evaluated. The evaluation results are shown in Table 4.

[0188] Table 4

[0189]

[0190] It can be seen from Table 4 that the maximum brightness of the liquid crystal display element in Examples 1 to 6 is greater than 2200 cd / m 2 , which is good, so the improvement of the display quality using the liquid crystal display element is excellent. In Comparative Example 1, the maximum brightness is less than 2200 cd / m 2 , is bad.

[0191] The difference in the orientation azimuth angle before and after AC driving in Application Examples 1 to 6, i.e., the angle Δ, is less than 0.1°, which is good. Therefore, the liquid crystal display element prepared using a liquid crystal alignment agent with high mechanical strength and high transmittance characteristics does not cause poor orientation, and a liquid crystal display element with better orientation can be obtained by using specific monomers and specific block polymerization methods.

[0192] <Evaluation Method of Liquid Crystal Cell Transmittance>

[0193] Using this liquid crystal unit, the sample was placed on the sample stage of the CA410 color analyzer at a constant temperature of 25°C, and the backlight brightness was set to 10000cd / m 2 Adjust the angle of the sample to the position with the minimum brightness. Apply AC voltage at a frequency of 30Hz from 0V to 10V, increasing by 0.1V. Test the brightness at each voltage and take the value with the maximum brightness. The maximum brightness value is greater than 2200cd / m 2 The transmittance is defined and evaluated as "good", and the maximum brightness value is less than 2200cd / m 2 The situation is defined and evaluated as "poor" transmittance.

[0194] <Evaluation method of liquid crystal orientation>

[0195] Using this liquid crystal cell, an AC voltage of 10 VPP was applied at a frequency of 30 Hz for 120 hours in a constant temperature environment of 25° C. Then, the pixel electrode and the counter electrode of the liquid crystal cell were short-circuited and left at 25° C. overnight.

[0196] After placement, the liquid crystal unit is set between two polarizing plates configured in a manner orthogonal to the polarization axes, the backlight is turned on without voltage application, and the configuration angle of the liquid crystal unit is adjusted to minimize the brightness of the transmitted light. Then, the rotation angle when the liquid crystal unit is rotated from the angle at which the second area of ​​the first pixel becomes darkest to the angle at which the first area becomes darkest is calculated as angle Δ. For the second pixel, the second area and the first area are also compared in the same way to calculate the same angle Δ. Then, the average value of the angle Δ values ​​of the first pixel and the second pixel is calculated as the angle Δ of the liquid crystal unit. The case where the value of the angle Δ of the liquid crystal unit is less than 0.1° is defined and evaluated as "good" liquid crystal orientation, and the case where the value of the angle Δ is greater than 0.1° is defined and evaluated as "poor" liquid crystal orientation.

[0197] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and the implementation modes. They can be fully applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily implemented. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to the specific details and the embodiments shown and described herein.

Claims

1. A polymer, characterized in that it is prepared from a diamine component comprising a structure represented by the following formula (1) and a dianhydride component comprising a structure selected from the following formula (3-1) and / or a structure represented by the following formula (3-2); In formula (1), X1 and X2 each independently represent a single bond or an alkyl group having 1 to 6 carbon atoms; Y1 and Y2 each independently represent one or more of -NHCO-, -CONH-, -OCO-, and -COO-; the structure represented by Ar is one or more structures selected from the following formulas (2-1) to (2-4); 2. The polymer according to claim 1, characterized in that The diamine component of the structure represented by the formula (1) is selected from one or more of the following structures; 3. The polymer according to claim 1, characterized in that The molar ratio of the diamine component to the dianhydride component is (1.08-1.15):

1.

4. A liquid crystal alignment agent, characterized in that: The polyamic acid-polyimide copolymer comprises a polyamic acid-polyimide copolymer and an organic solvent. The polyamic acid-polyimide copolymer is prepared by reacting the polymer described in any one of claims 1 to 3, the dianhydride compound of the structure of formula (3-1) or (3-2), and a substituted or unsubstituted diamine compound having 4 to 18 carbon atoms.

5. The liquid crystal alignment agent according to claim 4, characterized in that: The molar ratio of the dianhydride component in the polymer to the dianhydride compound is 1:(3-5).

6. The liquid crystal alignment agent according to claim 4, characterized in that: The molar ratio of the dianhydride compound to the diamine compound is 1:(1.02-1.08).

7. The liquid crystal alignment agent according to claim 4, characterized in that: The diamine compound includes a diamine compound containing a nitrogen heterocyclic ring, a diamine compound containing an ether bond, and a diamine compound containing a urethane bond in a molar ratio of 1:(1.3-1.8):(1.8-2.2).

8. A liquid crystal alignment film for a lateral electric field driven liquid crystal display element, characterized in that: This is obtained using the liquid crystal aligning agent as described in any one of claims 4 to 7.

9. A method for preparing a liquid crystal alignment film for a liquid crystal display element having a transverse electric field drive mode, characterized in that: The method comprises the following steps: step [I] of coating the liquid crystal alignment agent according to any one of claims 4 to 7 on a substrate having a conductive film for lateral electric field driving to form a coating film; Step [II], irradiating the coating film obtained in step [I] with polarized ultraviolet rays; and In step [III], the coating film obtained in step [II] is heated.

10. A lateral electric field driven liquid crystal display element, characterized in that: It includes the liquid crystal alignment film according to claim 8 or the liquid crystal alignment film manufactured by the preparation method according to claim 9.

Citation Information

Cited By

  • Polyimide precursor, liquid crystal aligning agent, liquid crystal alignment film, method for producing liquid crystal alignment film, and liquid crystal display element

    CN120590629A

  • Polyimide precursor, liquid crystal alignment agent, liquid crystal alignment film and manufacturing method, liquid crystal display element

    CN120590629B

  • High-adhesion and high-transparency liquid crystal polyimide film and preparation method thereof

    CN121718048A